2012
DOI: 10.1155/2013/864385
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel 5,7‐Dichloro‐1,3‐benzoxazole Derivatives

Abstract: A new class of 5,7-dichloro-1,3-benzoxazole derivatives4–11were synthesized by fusing 5,7-dichloro-2-hydrazino-1,3-benzoxazole3nucleus with aliphatic acids, active methylene compounds, and with selected esters to form heterocyclic ring systems like 1,2,4-triazoles, pyrazoles, and triazine moieties. The compound3on diazotization reaction affords the tetrazole compound. The synthesized compounds were characterized by1H NMR, IR, Mass, and13C NMR spectral data and screened for cytotoxic, antimicrobial, antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…The enhanced activity of both these compounds is by virtue of absence of substitution or due to electron donating methoxy group. [31] Watanabe et al (2015) reported the fabrication of 2-arylbenzoxazole that was used in Gram negative bacteria in order to detect nitro-ductase activity. Compound 2-(2-nitrophenyl)benzoxazole ( 21) exhibited best results against Gram negative bacteria and strain of S. aureus for nitroductase activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced activity of both these compounds is by virtue of absence of substitution or due to electron donating methoxy group. [31] Watanabe et al (2015) reported the fabrication of 2-arylbenzoxazole that was used in Gram negative bacteria in order to detect nitro-ductase activity. Compound 2-(2-nitrophenyl)benzoxazole ( 21) exhibited best results against Gram negative bacteria and strain of S. aureus for nitroductase activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Among the tested compounds, 1-(5,7-dichlorobenzoxazol-2-yl)-1Hpyrazolo [3,4-b]quinolin-6-ol (79) exhibited good scavenging effect 59.21% to 78.70%. [31] Gudipati et al (2011) fabricated a novel series of 12 derivatives of N-(benzoxazol-2-yl)-2-(7-or 5-substituted-2-oxoindolin-3-ylidene) hydrazinecarboxamide. These compounds were evaluated for their antioxidant activity by employing method of DPPH comparable to standard ascorbic acid.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Antimicrobial screening of the substituted pyrazolo [3,4-b]pyridines derivatives (PYR1-5) was performed by the Agar well diffusion method [38] and the dilution method (agar and liquid broth). The antimicrobial activity was evaluated using two different laboratory control strains of bacteria, i.e., Gram positive Bacillus subtilis CIP 5262, Gram negative, Escherichia coli CIP 53126.…”
Section: In Vitro Antibacterial and Antifungal Assaymentioning
confidence: 99%
“…The benzoxazole derivatives have been investigated for their inhibitory activity on eukaryotic DNA topoisomerase, and are known to exhibit antibacterial, , antitubercular, anticancer, antiparasitic, and anti-HIV activity (Figure ). In view of such therapeutic significance of these compounds, several methods targeting their individual synthesis, as well synthesis in combined form have been reported. These methods, however, suffer from drawbacks of being carried out in multiple steps; generate a large number of byproducts, long reaction time, use of harsh reagents and conditions, and low overall yield of the final product. With a view of harnessing the interesting biological properties of triazole and benzoxazole molecules, we attempted designing a simple synthetic route to construct these scaffolds.…”
Section: Introductionmentioning
confidence: 99%